Venice - Price, Gillian; Gale Group (London Dorling Kindersley Limited, 2015)
Provides background information on Venice; recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.
Venice's top 10 -- Around town -- Streetsmart.
Includes bibliographical references and index.
Keywords: Venice (Italy) -- Guidebooks